Exponential stability of stochastic cellular neural networks with mixed delays. Issue 19 (2nd October 2018) - Li, Xiaofei; Ding, Deng; Sang, Di
ABSTRACT: In this paper, almost sure exponential stability and p th moment exponential stability of stochastic cellular neural networks with mixed delays are investigated. Employing the methods of stochastic analysis, the Lyapunov's method, and useful inequality techniques, a sufficient condition ensuring the almost sure exponential stability and p th moment exponential stability is obtained. Two examples are given to illustrate this sufficient condition.